Effect of Egyptian Leek Leaf Extract Supplementation on Productive and Economic Performance of Broilers - Al-khalaifah, Hanan S.; Badawi, Mohamed E.; Abd El-Aziz, Reda M.; Ali, Mohamed A.; Omar, Anaam E. (Frontiers in Veterinary Science, 2020)
Antibiotic growth promoters have been used to improve growth and feed conversion in the poultry industry for a long time; however, they were banned because of several life-threatening side effects in animals, poultry, and humans. This work was carried out to investigate the effect of leek (Allium ampeloprasum var. kurrat) leaf extract (LLE) as a non-traditional growth promoter and feed additive on growth performance, carcass characteristics, serum biochemical parameters, and economic efficiency of broilers. Hubbard unsexed 1-day-old broilers (n = 250) were fed with diets supplemented with LLE for 42 days. The experimental chicks were randomly assigned to one of the five treatment groups varying in LLE quantity in diets: 0% (control), 0.05, 0.1, 0.15, and 0.2%, with five replicates per treatment (50 chicks/treatment or 10 chicks/replicate). Results showed that LLE supplementation improved (P < 0.05) different growth performance parameters. Furthermore, dietary LLE not only decreased serum total cholesterol, triglyceride, low-density lipoprotein, and glucose levels but also increased serum high-density lipoprotein level compared to the control diet. The weight percentages of dressing (P = 0.022) and liver (P = 0.041) showed a marked increase after the addition of LLE. Return, net profit, and collective efficiency measures were increased (P = 0.001) in all LLE groups compared with the control group. Broilers that fed on diets containing 0.2% LLE showed the highest growth and economic efficiency. It could be concluded that supplementation with LLE in broilers has growth-promoting effects, improved biochemical parameters, carcass quality, and promoted economic efficiency through maximizing both return and net profit.